KETERAMPILAN KONTEN KREATIF DIGITAL MARKETING MELALUI PELATIHAN E-COMMERCE DAN MERANCANG PESAN PERSUASIF BAGI KELOMPOK WANITA TANI (KWT) UMKM BUDIDAYA JAMUR TIRAM DI KELURAHAN LIMAU MANIS KOTA PADANG - Havifi, Ilham; Lubis, Muhammad Iqbal Abdi; Marta, Revi; Rafiuddin, M. Aqif; Adil, Dwi Honesti Kemala; Amni, Nurul Azizah (Jurnal Abdi Insani, 2025)
Business communication media is currently facing online-based global challenges through digital media. Small and medium enterprises (MSMEs) can utilize digital marketplaces (e-commerce) to expand their product sales. MSMEs need to use various promotional methods, such as creative content, videographics, colorful designs, and interesting stories on social media. Awareness of these digital opportunities is important to grow the business and reach a wider market. Digital media, such as websites, Instagram, and Tiktok, can convey information without restrictions on public access.Andalas University plays a role in helping MSMEs in the vicinity, such as in Limau Manis village, Padang, with a focus on oyster mushroom cultivation by the Women Farmers Group (KWT). KWT Tabiang Mandiri, which consists of 77 households, experiences problems with the quality of oyster mushrooms that easily change color and marketing problems. Digital marketing training, including the development of creative content and persuasive messages, is needed to increase the attractiveness of oyster mushroom products in e-commerce, so that products look more prominent and attract the attention of buyers. The first step was carried out in the form of assistance in making a Logo as a Persuasive Message for the KWT Oyster Mushroom Tabiang Mandiri MSME players, which was carried out skillfully and independently by MSME players with the Canva Pro Application. Then optimizing the use of appropriate technology for drying machines that prolong the storage period of Oyster Mushrooms so that they are durable when marketed in online media which requires delivery time to consumers. Urgency, digital marketing creative content skills through e-commerce training and designing persuasive messages for women farmer groups (kwt) umkm oyster mushroom cultivation in limau manis urban village, padang city